Generalized Laguerre-Apostol-Frobenius-Type Poly-Genocchi Polynomials of Higher Order with Parameters a, b and c (European Journal of Pure and Applied Mathematics, 2022)
In this paper, the generalized Laguerre-Apostol-Frobenius-type poly-Genocchi polyno- mials of higher order with parameters a, b and c are defined using the concept of polylogarithm, Laguerre, Apostol and Frobenius polynomials. These polynomials possess numerous properties including recurrence relations, explicit formulas and certain differential identity. Moreover, some connections of these higher order generalized Laguerre-Apostol-Frobenius-type poly-Genocchi poly- nomials to Stirling numbers of the second kind and different variations of higher order Euler and Bernoulli-type polynomials are obtained.
Keywords: poly-Genocchi polynomials; Laguerre polynomials; Apostol polynomial; Frobenius number; polylogarithm function; Appell polynomials; Euler ploynomials; Bernoulli polynomials